FAKTOR DAN ANALISIS KESALAHAN MEMBACA KOSAKATA YANG MENGGUNAKAN HURUF KATAKANA PADA MAHASISWA TINGKAT II (2016/2017) PRODI PENDIDIKAN BAHASA JEPANG FKIP UNRI - Desi Susriyani; Hadriana Hadriana; Nana Rahayu (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research is inteended to know what the mistakes made by students in reading vocabulary of Katakana and what are the underlying factors. The research uses quantitative descriptive method. The object of the research is the second grade (2016/2017) Japanese Language Education, Theahers Training and Education Faculty, University of Riau that consist 66 students. Data completion technique by giving a test and questionnaire. The test used ti find out what the mistakes made by students in reading vocabulary of Katakana, based on the data processing tests there are some mistakes such as students are still less master the letter that has similarity, students are still less master the letter that are marked Dakuten and students still lack understanding and dificult to distinguish the letter using small version. Then the questionnaire is to determine the underlying factors of the wind errors made by student. Based on the results of questinnaire data analysis can be concluded that the underlying factors of the wind errors made by students because of leaning strategies, the age of bilingualism and sociolinguistic situation.Keywords: Factors and Error Analysis, Reading, Katakana